Adenovirus DNA replication in vitro: characterization of a protein covalently linked to nascent DNA strands. - Challberg, M D (Proc Natl Acad Sci U S A, 1980)
The 5' terminus of each nascent daughter strand of adenovirus DNA replicated in vitro is covalently linked to a protein with an apparent Mr of 80,000. This protein may represent a precursor to the 55,000-dalton protein known to be linked to the 5' ends of mature adenovirus DNA strands. Partial proteolysis experiments indicate that the 80,000-dalton and 55,000-dalton proteins are structurally related. Furthermore, both proteins are attached to DNA by the same linkage: a phosphodiester bond between the beta-OH of a serine residue in the protein and the 5'-OH of the terminal deoxycytidine residue of the DNA. The role of the 80,000-dalton protein in adenovirus DNA replication is not yet clear, although one reasonable possibility is that it serves as the primer for daughter strand synthesis. IMAGES: